High temperature liquid chromatography of triazole fungicides on polybutadiene-coated zirconia stationary phase - Sanagi, M. Marsin; See, H. H.; Wan Ibrahim, Wan Aini; Abu Naim, Ahmedy (Elsevier Science B.V., 2004)
High temperature liquid chromatography using water-rich and superheated water eluent is evaluated as a new approach for the separation of selected triazole fungicides, hexaconazole, tebuconazole, propiconazole, and difenoconazole. Using a polybutadiene-coated zirconia column at temperatures of 100–150 oC, clear separations were achieved when 100% purified water was utilized as organic-free eluent. Excellent limits of detection down to pg level were obtained for the separation of the triazole fungicides under optimum conditions. Van’t Hoff plots for the separations were linear suggesting that no changes occurred in the retention mechanism over the temperature range studied.